2007
DOI: 10.1016/j.jtcvs.2006.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Bone or pleura? Primary pleural osteosarcoma

Abstract: Figure 2. Histologic examination demonstrated pink islands of osteoid with malignant cells showing atypical mitosis. There was no identifiable epithelial component and no mesothelioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…32,46,47 However, even recent reports of extraskeletal oesteosarcoma, one in a 73-year-old patient with known exposure to asbestos and another of a 76-year-old Navy engineer (with no data regarding asbestos exposure available), make no mention of immunohistochemical studies that might have suggested a diagnosis of mesothelioma. 48,49 Heterologous elements have rarely been described in other primary pleural sarcomas, such as malignant fibrous histiocytoma and malignant nerve sheath tumour. 50 We are not aware of pleural synovial sarcoma showing heterologous differentiation, but knowledge of the anatomical distribution and molecular studies demonstrating the SYT-SSX fusion gene would be helpful in that instance.…”
Section: Differential Diagnosis and Role Of Immunohistochemical Studiesmentioning
confidence: 99%
“…32,46,47 However, even recent reports of extraskeletal oesteosarcoma, one in a 73-year-old patient with known exposure to asbestos and another of a 76-year-old Navy engineer (with no data regarding asbestos exposure available), make no mention of immunohistochemical studies that might have suggested a diagnosis of mesothelioma. 48,49 Heterologous elements have rarely been described in other primary pleural sarcomas, such as malignant fibrous histiocytoma and malignant nerve sheath tumour. 50 We are not aware of pleural synovial sarcoma showing heterologous differentiation, but knowledge of the anatomical distribution and molecular studies demonstrating the SYT-SSX fusion gene would be helpful in that instance.…”
Section: Differential Diagnosis and Role Of Immunohistochemical Studiesmentioning
confidence: 99%
“…To our knowledge, only four cases of pleural osteosarcoma have ever been previously reported. [2][3][4][5] Here we present the case of a 64-yearold Japanese man with extraskeletal chondroblastic osteosarcoma that originally had arisen from the pleura. Both clinical and radiographic evaluations failed to reveal any tumor at other sites.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] All of these cases were male. The onset age of such patients was the sixth to seventh decade of life, in contrast to skeletal osteosarcoma, in which the peak incidence tends to be in the second decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…1 Among the various known types of extraskeletal osteosarcoma, only a few reports concerning primary pleural osteosarcoma were found. 3,4 We herein present an exceedingly rare case of pleural osteosarcoma occurring in a patient over 70 years of age.…”
Section: Introductionmentioning
confidence: 95%